Evaluating the outcomes of the ‘Circles of Adults’ intervention on adults supporting Looked After Children at risk of exclusion. - Turner, Jennifer (2014)
Looked After Children (LAC) are a potentially vulnerable population who are at risk of negative outcomes such as increased rates of exclusion from school linked to challenging behaviour. Although pupil behaviour may have negative implications for teachers, the literature on staff support suggests that group problem-solving approaches may be a useful mechanism of peer support which can consequently have direct and indirect effects for the school staff and pupils, respectively. One such approach is the ‘Circle of Adults’ (CoA) (Wilson & Newton, 2006) and was the focus of evaluation in the current study. Existing literature suggests CoA can enhance teacher capacity to respond to difficult behaviour. It was hypothesised that the CoA process would have positive effects upon teacher self-efficacy and causal attributions. A mixed-method design was employed, which combined a quasi-experimental component, to quantifiably measure any changes which occurred for the school staff, with a qualitative element to determine the participants’ views regarding the process and perceived outcomes. The study compared the participants’ outcomes from the four CoA sessions (n=10) with those attending two Personal Education Plan (PEP) meetings (n=5). The findings indicate that participation in the CoA intervention has no statistically significant effect upon school staffs’ causal attributions or perceived self-efficacy. However, there is some evidence to suggest that participation in the CoA leads to statistically significant increases in the perceived success of actions. Additionally, through a series of focus groups, participants reported that they valued the structure and visual representation of the CoA. However, school staff also highlighted functional difficulties in arranging support processes for LAC young people: in ensuring that relevant staff were present at the meetings and challenges associated with supporting LAC who often experience rapidly changing circumstances.